Design fabrication and testing of an arecanut dehusker - FEBI VARGHESE; Er. Jippu Jacob (Guide) (Tavanur 1993 Kelappaji College of Agricultrual Engineering and Technology)
Design fabrication and testing of an arecanut dehusker
Design fabrication and testing of an arecanut dehusker